Chronic Heart Failure: Does Cardiovascular Rehabilitation Promote Benefits to These Patients? - Petto , Jefferson; Oliveira , Edna Conceição de; Oliveira, Alice Miranda de; Santos , Larissa Ferreira dos; Souza , Pedro Elias Santos; Pinna Júnior, Bráulio José Baraúna de (JOURNAL OF CARDIAC ARRHYTHMIAS, 2026)
Introduction: Supervised cardiovascular rehabilitation (SCR) is an essential adjuvant therapy for patients with heart failure. However, the idea that its benefits are restricted to the early stages of heart failure persists in clinical practice. Objective: To describe how SCR positively impacted the functional capacity, functionality, clinical condition and quality of life of a patient with chronic heart failure (CHF) with an implantable cardioverter defibrillator (ICD). Case report: Female, sedentary, 67 years old, hypertensive for 30 years, with an ICD (for seven years), history of coronary artery disease and myocardial infarction, developed dilated ischemic heart failure of functional class III. She was referred by her arrhythmologist to the SRC service. She remained in treatment for seven months. The SRC program consisted of resistance exercises, cyclic exercises, and inspiratory muscle training, adjusted every two months. Results: After the cardiovascular rehabilitation period, we observed a 100% increase in ejection fraction (20% versus 40%), functional capacity (< 5 METs versus 6.8 METs), and quality of life (↑ 47%), as well as a decrease in blood pressure (180/90 versus 130/80 mmHg) and withdrawal of one drug (digoxin). Conclusion: An individualized SRC program can promote clinical and functional benefits and improve the quality of life of patients with chronic heart failure, indicating that not only patients with recent complications or in the early stages of heart failure can benefit from these benefits.